2021
DOI: 10.1021/acs.jpclett.1c01633
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen Activation and Transformation on Monometallic Niobium Boron Oxide Cluster Anions at Room Temperature: A Dual-Site Mechanism

Abstract: Dinitrogen activation and transformation at room temperature is a goal that has been long sought after. Despite that, it remains underdeveloped due to being a challenging research area and the need for a better mechanistic understanding. Herein, we report that well-defined NbB3O2 – gas-phase clusters can activate one N2 molecule and generate the products B3N2O– and B3N2O2 –, as applying mass spectrometry and theoretical calculations. This unusual N2 activation reaction results from the different functions of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 45 publications
0
25
0
Order By: Relevance
“…30–32 Therefore, using a cluster model to study the activation of nitrogen is an effective method. So far, the reaction of metal-containing clusters with N 2 has been widely studied, 33–53 while only a few studies are based on trimetallic clusters, such as pure metals (Mo 2 M, where M = Li, Na, K, Mg, and Ca), 54 metal carbides (V 3 C 4 − , 55 V 3− x Ta x C 4 − , 56 and FeV 2 C 2 − 57 ), hydrides (Co 3 D n − , 58 Ta 3 N 3 H 0,1 − , 59 and Rh 3 D n − 60 ), nitrides (Sc 3 N + 61 and Nb 2 LiNO 1–4 − 62 ) and sulfides (Ta 3 S n , 63 Nb 3 S n , and W 3 S n 64 ). Trimetallic clusters provide more coordination modes for N 2 adsorption than monometallic and bimetallic clusters and allow nitrogen to be dissociated for example with the end-on: side-on: side-on (ESS) coordination mode, which can only be realized in trimetallic (or larger) clusters.…”
Section: Introductionmentioning
confidence: 99%
“…30–32 Therefore, using a cluster model to study the activation of nitrogen is an effective method. So far, the reaction of metal-containing clusters with N 2 has been widely studied, 33–53 while only a few studies are based on trimetallic clusters, such as pure metals (Mo 2 M, where M = Li, Na, K, Mg, and Ca), 54 metal carbides (V 3 C 4 − , 55 V 3− x Ta x C 4 − , 56 and FeV 2 C 2 − 57 ), hydrides (Co 3 D n − , 58 Ta 3 N 3 H 0,1 − , 59 and Rh 3 D n − 60 ), nitrides (Sc 3 N + 61 and Nb 2 LiNO 1–4 − 62 ) and sulfides (Ta 3 S n , 63 Nb 3 S n , and W 3 S n 64 ). Trimetallic clusters provide more coordination modes for N 2 adsorption than monometallic and bimetallic clusters and allow nitrogen to be dissociated for example with the end-on: side-on: side-on (ESS) coordination mode, which can only be realized in trimetallic (or larger) clusters.…”
Section: Introductionmentioning
confidence: 99%
“…66 A special case that a ligand atom such as boron and carbon functions as a metal atom was recently reported for the μ 2η 1 :η 2 -N 2 mode in the adsorption complexes NbB 3 O 2 N 2 − and NbCO 2 N 2 − . 76,78 Moreover, a new coordination mode, distorted-μ 2 -η 1 :η 2 -N 2 (Scheme 2c), arising from the disparate electronic structures of 5d ETM and 3d LTM, was revealed to be vital for the NN cleavage by FeTaC 2 − . 75 For most of the reported polynuclear metal clusters, such as Ta 3 S 0−3 , 68 Ta 4,6 + , 47,70 V 3−x Ta x C 4 − (x = 0−3), 73,85 Sc 3 N + , 77 and FeV 2 C 2 − , 74 N 2 binding in the trinuclear end-on/end-on/sideon (μ 3 -η 1 :η 1 :η 2 -N 2 , Scheme 2d) and end-on/side-on/side-on (μ 3 -η 1 :η 2 :η 2 -N 2 , Scheme 2e) modes is the prevalent paradigm for N 2 cleavage.…”
mentioning
confidence: 99%
“…Quite recently, we reported that NbH 2 − anions can form N−C bonds directly from simple N 2 and CO 2 at room temperature, which is the only gas-phase species that can directly couple N 2 and CO 2 , to the best of our knowledge, and a novel N 2 activation mechanism, that is metal−ligand activation (MLA), is proposed. 17 The laser ablation-generated AuNbBO − cluster anions were generated by seeding He in the cluster generation gas and mass-selected to react with N 2 , 15 N 2 , CO 2 , or C 18 and AuNbBON 2 H 2 O − clusters were also obtained, which can be attributed to the reactions of residual water impurities with AuNbBO − and the newly formed AuNbBON 2 − , respectively. To study the reaction of the AuNbBON 2 − cluster with CO 2 , the AuNbBO − cluster was initially reacted with the N 2 seeded in the cooling gas (He).…”
mentioning
confidence: 99%
“…17 As opposed to the generally reported metal−metal activation (MMA) mode in both condensed-phase and gasphase systems, we proposed the metal−ligand activation (MLA) mode. 18 One distinct advantage of the MLA mode is that the produced N atom can be removed immediately after activation, avoiding the formation of dead-end transition metal nitrides. In the N 2 and CO 2 coupling reaction by AuNbBO − , the MLA mode is also adopted.…”
mentioning
confidence: 99%